2016
DOI: 10.1016/j.appdev.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Peer relations, parental social coaching, and young adolescent social anxiety

Abstract: Links between peer relationship difficulties, parental social coaching, and social anxiety were examined among young adolescents (N = 80). In a lab protocol simulating peer stress, adolescents led a 3-min conversation, while ostensibly being evaluated by (fictitious) peer judges. Parental coaching was measured via observed cognitive framing and advice-giving; parents also reported on their facilitation of access to peers, and their adolescent's peer victimization and rejection. Social anxiety was measured thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 66 publications
2
23
1
Order By: Relevance
“…Both boys and girls engage in doxing, although we found the latter to be significantly more likely to conduct social doxing via SNSs. Girls were found to have more social anxiety than boys in previous research [28,29], which may explain their intentions of social doxing. Even though we identified no gender differences in hostile doxing, significantly more boys than girls targeted personally identifiable and physical location information and other types of private and sensitive data.…”
Section: Discussionmentioning
confidence: 75%
“…Both boys and girls engage in doxing, although we found the latter to be significantly more likely to conduct social doxing via SNSs. Girls were found to have more social anxiety than boys in previous research [28,29], which may explain their intentions of social doxing. Even though we identified no gender differences in hostile doxing, significantly more boys than girls targeted personally identifiable and physical location information and other types of private and sensitive data.…”
Section: Discussionmentioning
confidence: 75%
“…Adolescents with social anxiety may prefer loneliness because they think that they are unwanted and evaluated negatively by others. When adolescents in much need of peer support are rejected by their peers, they experience more social anxiety (Su, Pettit & Erath, 2016).When the emphasis on peer relationships during adolescence is taken into account, an adolescent is likely to experience loneliness and negative affects upon being unable to initiate and sustain relationships. On the other hand, adolescents with high levels of social anxiety may feel lonely upon thinking that this situation will not change for the better as they often experience anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, negative experiences with peers and lack of self-confidence in an individual's skills may lead to social anxiety and social withdrawal (Inderbitzen, Walters & Bukowski, 1997). Su, Pettit & Erath's (2016) study on adolescents showed that adolescents rejected by friends and less guided by families experienced more social anxiety. Individuals with high levels of social anxiety have been observed to avoid social environments and to have difficulties initiating and sustaining friendships.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, models of parental social coaching have been applied to older children and young adolescents. For example, observations of parental prosocial behavioral advice (e.g., find common ground) and benign cognitive framing (e.g., recall times when peers have been friendly) during a parent-adolescent discussion about responding to peer rebuff each independently and concurrently predicted lower social anxiety among early adolescents (Su, Pettit, & Erath, 2016). Moreover, parent-reported prosocial behavioral advice and benign cognitive framing in response to hypothetical peer-problem vignettes independently and prospectively predicted young adolescents’ higher peer acceptance, as rated by parents and teachers, controlling for earlier levels of peer acceptance (Gregson, Tu, Erath, & Pettit, 2017).…”
Section: Addressing Peer Victimization Head-on: Direct Prpvmentioning
confidence: 99%